The origins of postmodern moral relativism - Deng, Gang (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
Postmodernism, which emerged in the 1960s, involves a wide range of fields and carries out all-round critical reflections on the foundation, tradition and other aspects of the development of modern civilization. Postmodern morality came into being with the popularity of postmodernism in western countries. It features obvious “de-universality” and provides a new mirror for reflections on modern morality. Its progressive significance cannot be ignored. However, some postmodern moral concepts are becoming increasingly relativistic, even going to extremes, bringing about disturbances to society. Tracing the root of moral relativism back to ancient times based on the great history of its development, this study first sorts out the same gene of ancient Western moral relativism – using “skepticism” as a weapon against authority and dogmatism, and points out that the key of using moral relativism lies in seeking the proper limit of “skepticism”. Then it draws forth the fact that postmodern morality started with “skepticism” and prevailed because of its “relativism”, pointing out that some postmodern morality moved toward moral relativism because of persistence in “skepticism”, while some fall into a state of moral nihility by radicalising “skepticism”. If a craftsman wants to do good work, he must first sharpen his tools. This study concludes with suggestions on how to use the “skepticism” of postmodern morality.